2003
DOI: 10.1161/01.str.0000098649.39767.bc
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Arterial Dissection

Abstract: Background and Purpose-Cervical arterial dissection is a major cause of stroke in young adults, yet despite standard treatment with anticoagulants or antiplatelet drugs, its management remains uncertain. The goal of this study was to assess the natural history of the disorder and to decide on the feasibility of a therapeutic trial. Methods-Collaborating members of the Canadian Stroke Consortium prospectively enrolled consecutively referred patients with angiographically proven acute vertebral or carotid arteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
0
10

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(103 citation statements)
references
References 39 publications
2
91
0
10
Order By: Relevance
“…As no reliable data from randomized trials were available, it is not possible to draw any definite conclusions. 4,37 Reported nonrandomized studies, likewise, have not shown evidence of a significant difference between anticoagulants and antiplatelets.…”
Section: Management Optionsmentioning
confidence: 99%
See 2 more Smart Citations
“…As no reliable data from randomized trials were available, it is not possible to draw any definite conclusions. 4,37 Reported nonrandomized studies, likewise, have not shown evidence of a significant difference between anticoagulants and antiplatelets.…”
Section: Management Optionsmentioning
confidence: 99%
“…7 This incidence appears to be significantly different from the 10.4% annual recurrence rate reported in adults. 4 The type of antithrombotic therapy (heparin, warfarin, or antiplatelet) and its duration are controversial. Thus, there is no evidence that anticoagulation is superior to observation or antiplatelet therapy in children.…”
Section: Management Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 It has been found that the combined recurrence of stroke and death after successful treatment of cervical artery dissection causing stroke is 10-15 per cent. 16 There are no current figures available on the mortality or recurrence of stroke following thoracic aortic dissection.…”
Section: Arterial Dissection and Strokementioning
confidence: 99%
“…[1][2][3][4] It is estimated that 1 to 1.5 per 100 000 individuals in the United States will experience this condition. 5,6 Common presenting symptoms are headache and neck pain; thus, many of these patients may present for chiropractic care.…”
Section: Introductionmentioning
confidence: 99%